Health economics of home-based circumcision services: A community-based assessment of affordability - Yulita Eka Fitri; Maya Sartika (Science Center Group, 2026)
Background: Home-based circumcision may improve service accessibility by reducing travel requirements, waiting time, and disruption of household activities; however, its affordability cannot be determined solely from the procedural fee because household resources and indirect economic consequences may substantially influence financial burden. Objective: This study aimed to assess the affordability of home-based circumcision services from a community perspective and to examine bivariate associations between household, service-related, and socioeconomic characteristics and perceived affordability. Methods: A community-based analytical cross-sectional study was conducted among 423 parents or legal guardians of children who received home-based circumcision services in Ogan Komering Ulu Regency, South Sumatra, Indonesia, from January to June 2026. Affordability was assessed using the 25-item Home-Based Circumcision Affordability Questionnaire (HBCAQ) and a household cost-to-income ratio. Descriptive statistics and bivariate analyses were performed. Associations with the continuous HBCAQ score were estimated using separate unadjusted simple linear regression models. Results: The mean standardized HBCAQ score was 74.6 ± 11.8, with 54.1% and 33.3% of households reporting moderate and high affordability, respectively. Median total household expenditure was IDR 820,000 (IQR 680,000–970,000), and the median cost-to-income ratio was 8.7% (IQR 5.4–13.8). Forty percent of households spent at least 10% of monthly household income on the circumcision episode. In bivariate analyses, higher monthly household income, greater estimated transportation/time savings, urban residence, and diploma/bachelor-level education or higher were associated with higher affordability scores, whereas higher total circumcision costs, a greater number of dependent children, and additional post-procedure healthcare utilization were associated with lower affordability scores (all p ≤ 0.002). Conclusion: Home-based circumcision was perceived as moderately to highly affordable and offered meaningful convenience and time-saving advantages, although the relative financial burden varied across households. The observed bivariate relationships suggest that household economic capacity, service costs, residence, family dependency, and post-procedure healthcare use should be considered when designing transparent and equitable home-based circumcision services.